The impact of the 2004 EU-enlargement on enterprise performance and exports of service enterprises in the German eastern border region - Nils Braakmann; Alexander Vogel (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2009)
We consider the impact of the 2004 EU-enlargement on enterprise performance and the exporting behavior of German service enterprises in Germany's eastern border region. Our results from regression adjusted difference-in-differences-estimators combined with matching and panel data from official statistics suggest that the EU-enlargement resulted in a decline by circa 1 percent in the turnover and the profitability of large enterprises in the border region, respectively. For small enterprises, we find an annual increase in turnover by 2.7% in both 2004 and 2005 and an annual decrease in profitability by 1.8 and 2.6 percentage points in 2004 and 2005 respectively.
Keywords: F15; L80; 330; EU-enlargement; enterprise performance; exports